Influence of Entrepreneurship Manifestation Factor on Organisational Innovation: The Role of Corporate Entrepreneurship and Imperative Innovation Culture - Kim, Jiyeon; Park, Min Jae (Journal of Entrepreneurship, 2022)
The importance of corporate entrepreneurship is continuously highlighted as a crucial potential corporate growth strategy that seeks continued growth opportunities. Corporate entrepreneurship is perceived as a critical element of corporate performance, so studies on key internal factors that may affect the manifestation of such entrepreneurship within an organisation are gaining increasing attention. This is because an innovative organisational environment is vital for invigorating corporate entrepreneurship in the organisation. This study aims to show how managers and employees can design and run their organisations in a way that is conducive to innovation, value-creation and continued growth by examining how internal organisational support and imperative innovation culture manifests corporate entrepreneurship and supports organisational innovation. This study analysed how key internal factors affecting the manifestation of corporate entrepreneurship influence the organisational innovation of 229 Korean companies. This study intends to determine the internal factors that support and strengthen corporate entrepreneurship by shedding light on which of them affect the manifestation of corporate entrepreneurship necessary to nurture and develop more intrapreneurs. This research also aims to analyse how imperative innovation culture moderates the relationship among innovation activity, organisational innovation and risk-taking.
Keywords: Corporate entrepreneurship; innovation culture; manifestation factor; organisational innovation; PLS; SEM